A system dynamics model for regulatory impact assessment in transport of dangerous goods. Issue 3 (3rd July 2021) - Çelebi, Dilay
ABSTRACT: The purpose of this study is to identify the issues related to implementation process of "European Agreement on the International Transport of Dangerous Goods by Road (ADR)" regulations in Turkey over a system dynamics model. The proposed model is used for assessing potential impacts of relevant regulations on dangerous goods transportation sector, in terms of road safety, operational effects, and economical consequences. We found that the incident rates and number of casualties fall rapidly because of the safety measures brought by ADR. However, the expected decrease in accident costs is far below the expected additional operational costs that ADR brings. Our results contribute to the literature by providing a system dynamics based framework for analysis of integration issues related to DG transportation regulations, which would further serve for building up of the strategies related to local, national and international policies.